PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING BERBANTU ALAT PERAGA TERHADAP KONSEP IPA SD NEGERI 01 PEMULUTAN - Wahyuni Diah Pratami; Lukman Hakim; Rury Rizhardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine whether there is an influence of the Contextual Teaching And Learning Learning Model Assisted by Teaching Aids on the Concept of Elementary Science in grade V students. This study uses the Quasi Experimental Design research method with a Nonequivalent Control Group Design research plan. The population in this study was all grade V students of SD Negeri 01 Pemulutan. The sample used in this study was Total Sampling with class V. A as many as 26 students as experimental class and class V. B as many as 27 as control class. The data collection techniques used in this study were observation, tests and documentation. The analytical technique used in this study used a t-test. In the post-test results of the control class and experimental class showed a significant difference after the application of the Contextual Teaching and Learning learning model, the data analysis obtained was <0.001< 0.05, then rejected and accepted. So after testing, it can be concluded that there is a significant influence on the application of the Contextual Teaching and Learning (CTL) Learning Model Assisted by Teaching Aids on the Science Concept of SD Negeri 01 Pemulutan.